EVALUATION OF TL1A DIAGNOSTIC AND PROGNOSTIC VALUES IN ANKYLOSING SPONDYLITIS PATIENTS; IN SULAYMANIYAH GOVERNORATE - Tofiq, Dana Mohammed (European Scientific Journal, ESJ, 2015)
Background: Ankylosing spondylitis is a chronic inflammatory disorder primarily involving the sacroiliac joints and spine. It is associated with both articular and extra-articular clinical manifestations, including peripheral arthritis, enthesitis, and anterior uveitis. Objectives: To compare the serum levels of tumor necrosis factor-like ligand 1a (TL1A) in ankylosing spondylitis patients and the apparently healthy persons; and to find out the association between the cytokine level and ankylosing spondylitis disease activity and spinal mobility. Patients and Methods: Cross-sectional analytic study conducted in the division of rheumatology/Shaheed Hemin general hospital, in Sulymaniyah city from (April 2015 to September 2015), on 45 ankylosing spondylitis patients with ages ranged between 17 to 52 years. The patients interviewed, fully examined, and classified to anti-TNF treated (n=26) and non-biologic therapy treated (n=19). Then investigated for the serum levels of TL1A and the results were compared with those of 45 age and gender matched apparently healthy persons. The cytokine levels also compared with the disease activity and spinal mobility parameters. Results: The serum levels of TL1A in ankylosing spondylitis patients were significantly higher than those of the healthy subjects, with mean and standard deviation values of (428.4±285.7 pg./ml), (217.6±64 pg. /ml) respectively, the serum levels of TL1A in non-biologics treated ankylosing spondylitis patients were significantly higher than those of the healthy subjects, with mean and standard deviation values of (576.6±337.4 pg./ml), (217.6±64 pg./ml) respectively, and for anti-TNF treated ankylosing spondylitis patients mean and standard deviation values of (320.1±181.2 pg./ml), (217.6±64 pg./ml) respectively, with (P values < 0.001). Conclusions: Serum TL1A is up-regulated in ankylosing spondylitis, associates with disease activity; and isn’t normalized by anti-TNF therapy, suggesting that TL1A may be of pathogenic and potentially of therapeutic importance in ankylosing spondylitis.